Adamantine - Foyle, Naomi (Book collections on Project MUSE., 2019)
From odes to remarkable artists and activists, to a lyrical response to her own breast cancer treatment, Naomi Foyle's third collection celebrates women's tenacity and luster. Deploying a dazzle of forms from the sonnet to visual poetry, the book's opening sequence honours the achievements of women as diverse as Mohawk writer and performer Tekahionwake, gothic chanteuse Nico, and the mothers of West Belfast. From Foyle's concern with the Middle East spring tributes to Palestinian and Israeli prisoners of conscience - and to Arabic poetry. In its imagistic intensity and emotional vulnerability, the book's final sequence, The Cancer Breakthrough, pays homage not just to the poet's resilience and relentless creativity, but also to the power of loving community.